The Renewal of the Religious Discourse and the Evaluation of Human Behavior in Various Spheres in the Light of Prophetic Sunnah - Al-Azzam, Najah (Dirasat: Shari’a and Law Sciences, 2020)
This research deals with an important issue related to the renewal of religious discourse, which is the evaluation of human behavior in different areas of life from the reality of the Prophetic Sunnah. The study followed the descriptive and inductive method, by collecting the noble prophetic texts received regarding the evaluation of human behavior and its control after extracting them from Bukhari, Muslim, and other sources such as the Sunnah of Abu Dawud, the Sunnah of Tirmidhi, and followed the analytical method of the hadiths chosen to serve the reality of development and change in human life, and devising the prophetic approach in dealing with them and how to adjust and deal with them in light of our reality. It was found that the prophetic text is valid for every time and place, and that renewal in it is only by returning to it and arriving at the correct understanding of its content. The renewal is also in the Muslim’s diligence in modifying his/her behavior and controlling his/her behavior, and in his/her re-understanding of Sunnah with its sensory or moral data and indications, and linguistic or rhetorical hints that might guide him/her to the correct method that the Prophet -PBUH- intended.